Использование многомерного индексирования для повышения точности поиска научной информации (Библиосфера, 2010)
The author describes the practical of the research library in the Institute of Semiconductor Physics with information retrieval classification systems and the advantages of the use of multidimentional indexing for research documents from the view point of information retrieval and search on the particular thematic requests.